A relational theory of world politics - Qin, Yaqing, 1953- (Cambridge : Cambridge University Press, 2018)
Drawing on Chinese cultural and philosophical traditions, this book offers a ground breaking reinterpretation of world politics from Yaqing Qin, one of China's leading scholars of international relations. Qin has pioneered the study of constructivism in China and developed a variant of this approach, arguing that culture defined in terms of background knowledge nurtures social theory and enables theoretical innovation. Building upon this argument, this book presents the concept of'relationality', shifting the focus from individual actors to the relations amongst actors. This ontology of relations examines the unfolding processes whereby relations create the identities of actors and provide motivations for their actions. Appealing to scholars of international relations theory, social theory and Chinese political thought, this exciting new concept will be of particular interest to those who are seeking to bridge Eastern and Western approaches for a truly global international relations project.
Title from publisher's bibliographic system (viewed on 24 Apr 2018).
Keywords: World politics; International relations; Constructivism (Philosophy); Social sciences -- Philosophy; Multiculturalism